A new species and redescription of two species of Euseius Wainstein (Acari: Phytoseiidae) from Cerrado biome areas in Brazil - Demite, Peterson R.; Cavalcante, Ana C. C.; Dias, Monique A.; Lofego, Antonio C. [UNESP] (My University, 2016)
A new species Euseius uai sp. n. Demite & Lofego is described from the Minas Gerais State, Brazil. Euseius errabundus De Leon is recorded for the first time in Brazil and E. unisetus Moraes & McMurtry is rediscovered. Both were collected in Goiás State, Brazil. A dichotomous key for the Brazilian Euseius species is presented.
Keywords: Amblyseiinae; Euseiini; natural vegetation; redescription; rediscovery